MCAM knockdown impairs PPARγ expression and 3T3-L1 fibroblasts differentiation to adipocytes - Gabrielli, Matias (2018)
We investigated for the first time the expression of melanoma cell adhesion molecule (MCAM) and its involvement in the differentiation of 3T3-L1 fibroblasts to adipocytes. We found that MCAM mRNA increased subsequent to the activation of the master regulator of adipogenesis, PPARγ, and this increase was maintained in the mature adipocytes. On the other hand, MCAM knockdown impaired differentiation and induction of PPARγ as well as expression of genes activated by PPARγ. However, events that precede and are necessary for early PPARγ activation, such as C/EBPβ induction, β-catenin downregulation, and ERK activation, were not affected in the MCAM knockdown cells. In keeping with this, the increase in PPARγ mRNA that precedes MCAM induction was not altered in the knockdown cells. In conclusion, our findings suggest that MCAM is a gene upregulated and involved in maintaining PPARγ induction in the late but not in the early stages of 3T3-L1 fibroblasts adipogenesis.